Independent control over multiple cell types in space and time using orthogonal blue and red light switchable cell interactions - Yüz, Simge G.; Ricken, Julia; Wegner, Seraphine V. (Advanced science, 2018)
Independent control over multiple cell-material interactions with high spatiotemporal resolution is a key for many biomedical applications and understanding cell biology, as different cell types can perform different tasks in a multicellular context. In this study, the binding of two different cell types to materials is orthogonally controlled with blue and red light providing independent regulation in space and time. Cells expressing the photoswitchable protein cryptochrome 2 (CRY2) on cell surface bind to N-truncated CRY-interacting basic helix-loop-helix protein 1 (CIBN)-immobilized substrates under blue light and cells expressing the photoswitchable protein phytochrome B (PhyB ) on cell surface bind to phytochrome interaction factor 6 (PIF6)-immobilized substrates under red light, respectively. These light-switchable cell interactions provide orthogonal and noninvasive control using two wavelengths of visible light. Moreover, both cell-material interactions are dynamically switched on under light and reversible in the dark. The specificity of the CRY2/CIBN and PhyB/PIF6 interactions and their response to different wavelengths of light allow selectively activating the binding of one cell type with blue and the other cell type with red light in the presence of the other cell type.